Pengembangan Media Papan Huruf untuk Meningkatkan Motivasi Belajar Siswa Kelas 1 SDN Natakupe: Development of Letter Board Media to Enhance Learning Motivation for 1st Grade Students at SDN Natakupe - Pare, Maria Ines Teresa; Beku, Veronika Yuliana; Dhiu, Maria Isabela; Sayangan, Yohanes Vianey (Universitas Tidar, 2025)
This research aims to develop learning media in the form of a letterboard designed to increase the learning motivation of grade 1 students of SDN Natakupe, especially in learning Indonesian, and to test its feasibility. Student learning motivation is a major concern because it plays an important role in supporting an effective learning process. This research focuses on the question,